"People live in their heads a lot": Polymedia, life course, and meanings of home among Melbourne's older Irish community. Issue 1 (2nd January 2017) - Ballantyne, Glenda; Burke, Liam
Abstract: Research across a number of disciplines demonstrates that digital technologies have intensified migrants' connections to both old and new homelands. Yet to be explored, however, is how this interconnectedness intersects with shifting conceptions of "home" over the life course. The research presented here helps fill this gap by drawing on surveys and semi-structured qualitative interviews conducted with Irish immigrants to Australia, now in their 60s, 70s, and 80s, who left Ireland prior to the emergence of new media. The article charts a trajectory across three phases of the migrant life course: "leaving home, " characterized by feelings of dislocation from Ireland and an involvement in the local Irish "ethnic village"; "at home, " characterized by withdrawal from ethnic community involvements under the pressure of family and work responsibilities; and "going home, " characterized by a desire to reconnect with origins, both locally and transnationally. Our findings suggest that age-related social circumstances and existential concerns have played an important role in shaping older migrants' use of new media to stay "connected."